Molecular and phylogenetic analysis of the filarial nematode Micipsella numidica from the hare Lepus europaeus in Italy. Issue 4 (30th June 2015) - Gabrielli, S.; Galuppi, R.; Fraulo, M.; Savini, F.; Morandi, B.; Cancrini, G.; Poglayen, G.
Abstract: The genus Micipsella comprises three species of filariae to date identified in lagomorphs only, whereas the other genera belonging to the subfamily Splendidofilariinae are described as parasites of birds, reptiles and mammals. In the present study seven specimens of Micipsella numidica (Seurat, 1917), collected from the hare Lepus europaeus in Italy, were characterized genetically by molecular amplification of the mitochondrial genes (12S rDNA; cox1 ) and the 5S rDNA gene spacer region. Phylogenetic trees inferred using available sequences from filariae and those identified in this study evidenced a close relationship between M. numidica and Splendidofilariinae of other mammals and reptiles ( Rumenfilaria andersoni and Madathamugadia hiepei). The present findings, apart from adding new data about the hosts in Italy, support the taxonomic position of M. numidica and highlight the substantial biological and molecular differences existing between Splendidofilariinae and other Onchocercidae. The study also contributes to our knowledge of the molecular/genetic diagnosis of filarial parasites of veterinary and medical concern in any vertebrate or invertebrate host.